Platform competition and strategic trade‐offs for complementors: Heterogeneous reactions to the entry of a new platform - Loh, Johannes; Elsas-Nicolle, Ambre (Strategic Management Journal, 2026)
Abstract Research Summary We study how the entry of a rival platform affects the strategies of the incumbent's complementors. The latter face a trade‐off: While the entry threatens their benefits from indirect network effects, it also allows them to escape intense within‐platform competition. Studying Epic Games' entry into the PC video game market—until then dominated by Steam—we show that this trade‐off does not resolve uniformly, driving heterogeneity in strategic reactions. Complementors with weaker strategic resources (independent developers) were more likely to multihome and became less responsive to the incumbent's attempts to orchestrate collective action through platform‐wide sales promotions. In contrast, complementors more reliant on indirect network effects (multiplayer developers) were less likely to multihome and became more responsive to orchestration attempts. Managerial Summary As competition between digital platforms intensifies, complementors—firms that provide complementary products or services—must adjust how they engage with platform owners. The entry of a rival platform creates both opportunities and risks: it offers an alternative with less intense competition but also fragments the user base that underpins network benefits. We find that these opposing effects shape complementors' behavior differently. Those with fewer strategic resources are more likely to join the new platform and become less willing to follow the incumbent's coordinated initiatives. In contrast, complementors whose products rely strongly on network effects tend to remain with the incumbent and cooperate more closely with its orchestration efforts. For managers, this highlights that platform competition not only shifts market dynamics but also reshapes the motivations and strategies of heterogeneous complementors.